2017
DOI: 10.1177/1933719116667221
|View full text |Cite
|
Sign up to set email alerts
|

The Synergic In Vitro Tocolytic Effect of Nifedipine Plus Ritodrine on Human Myometrial Contractility

Abstract: Many pharmacological agents have been investigated to manage preterm labor; we postulate that a combination of tocolytic drugs may achieve a better effect in the prevention of uterine contractions without dose-dependent adverse effects. The aim of this study was to evaluate the inhibitory effect of dual combinations of tocolytics in vitro. Human myometrium was obtained during elective cesarean sections (term without labor; n = 40). Myometrial strips were placed in organ baths for the measurement of isometric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
(47 reference statements)
0
6
1
2
Order By: Relevance
“…Test substances were applied on spontaneously contracting human myometrial samples. This was contrary to methods of other investigators using a model of oxytocin-induced contractions to analyse tocolytic effects [12][13][14]. In preliminary experiments, however, we found that this approach was not feasible for a study design including atosiban as oxytocin-induced contractions were already maximally supressed by the oxytocin receptor antagonist atosiban (data not shown).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Test substances were applied on spontaneously contracting human myometrial samples. This was contrary to methods of other investigators using a model of oxytocin-induced contractions to analyse tocolytic effects [12][13][14]. In preliminary experiments, however, we found that this approach was not feasible for a study design including atosiban as oxytocin-induced contractions were already maximally supressed by the oxytocin receptor antagonist atosiban (data not shown).…”
Section: Discussioncontrasting
confidence: 74%
“…The in vitro model is well established at our institute and internationally accepted in the literature as a means to evaluate the effect of single or dual tocolysis [6,7,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Результаты этого исследования указывали на перспективность применения блокаторов ОР при ПР. На изолированном миометрии беременных также было показано, что атозибан снижает утеростимулирующий эффект окситоцина [19,32,37,38], в том числе совместно с нифедипином [38] или с сульфатом магния [37]. В опытах с беременными крысами показано [39], что под влиянием атозибана уменьшается содержание ОР в миометрии, что трактуется как проявление десенситизации.…”
unclassified
“…Ряд авторов [37,38,51]признают целесообразность применения атозибана в комплексе с другими токолитиками, в том числе с нифедипином, с агонистами β 2 -АР, например, с ритодрином, с нитроглицерином или с сульфатом магния. Преимущество такой комбинированной токолитической терапии было продемонстрировано в опытах с изолированным миометрием беременных женщин в отношении окситоцинвызванных сокращений [37,38]. Полагают [53], что после успешного лечения угрожающих ПР с помощью атозибана рационально применение прогестерона.…”
unclassified